The comparison of seroconversion rates among different varicella vaccines administered Turkish children; MAV/06 and vOka - Zuhal Umit; Zumrut Sahbudak Bal; Aysin Zeytinoglu; Tansu Gulbahar Aydogan; Ozlem Bag; Gizem Guner Ozenen; Ferda Ozkinay; Zafer Kurugol (Human Vaccines & Immunotherapeutics, 2021)
Varicella is a vaccine-preventable disease, and the incidence of varicella has declined since the introduction of varicella vaccine campaigns. A wild type of varicella zoster virus (VZV) was isolated from a 33-month-old child with varicella in Korea in 1989, a different strain (MAV/06). A live-attenuated varicella vaccine containing strain (MAV/06), Suduvax®, was developed in South Korea in 1994. Turkey introduced the varicella vaccine containing the MAV/06 strain (Varicella Vaccine-GCC, Green Cross, South Korea) in January 2019. Therefore, we aimed to compare the seroconversion rates among MAV/06 vaccine- and vOka-administered children. We prospectively collected blood samples from 98 received vOKA and 98 received MAV/06 children 6 weeks after administration, and seroconversion rates were determined by an indirect fluorescence assay (Anti-VZV IIFT IgG, Euroimmun, Germany). Seroconversion rate was significantly higher in vOka group than MAV/06 group (82.7% vs. 64.3%; p = .004). Of the children vaccinated with vOka strain, 17 children did not develop antibodies, 12 were weakly positive, and the remaining 69 children were strongly positive. Of the children who were administered MAV/06 strain, 35 were negative, 20 were weakly positive, and 43 were strongly positive. In conclusion, this study demonstrated that MAV/06 varicella vaccine had lower seroconversion rates and the strong seropositive cases were less common than vOka-administered children. Larger and prospective studies are needed.